Understanding investors' behavior from the variation of sukuk spreads - Abdul Rahman, Maya Puspa; Kassim, Salina (Red Money, 2014)
The mechanics of Sukuk investment are a mysterious and complicated subject for many investors. From the Sukuk structure and the pricing methodology, to its risks and trading strategy, we often leave it to the experts to handle. However with its position as an essential asset class in the mandate of Shariah funds, understanding Sukuk structure is important for all participants.